The orthogonal essence of the antique city - Kolesnikov, Alexander; Tatarinov, Maxim (project baikal, 2025)
This article examines the formation and development of the orthogonal planning structure of the ancient cities of the Hellenistic era and Rome. It reveals the development line from the order system and rectangular peristyle public and residential spaces to a complete orthogonal urban structure. On this basis, the authors put forward the idea of the orthogonal essence of the antique city, which combines these elements on the basis of the principle of simplicity and equality. Architectural approaches are shown to locate the city on the ground and combine its various elements into a single organism diversifying the layout by combining several orthogonal systems. The region of study is Asia Minor, the area of active economic and social development of the antiquity, which contained poleis with a wide variety of layouts, size and composition, interesting for the analysis of their urban structure. The authors give examples of the layouts of famous cities such as Priene, Magnesia, Knidos, Sagalossos, as well as new material for the planning of Pergamon.
Keywords: orthogonal; Hippodamian system; Order; Polis; Hellenistic; Roman